Effects of micro/nano CeO2 on the microstructure and properties of WC-10Co cemented carbides. (February 2021) - Cai, Huang; Jing, Wenwen; Guo, Shengda; Liu, Lei; Ye, Ying; Wen, Yan; Wu, Yunxuan; Wang, Shuilong; Huang, Xing; Zhang, Jianbo
Abstract: WC-10Co cemented carbide with micro/nano CeO2 additives was obtained through powder metallurgy technology. The effects of CeO2 grain size on the structure and performances were investigated by scanning electron microscope, X-ray diffraction, mechanical properties testers and friction testing machine. The results showed that the grain size of WC decreased after adding micro/nano CeO2, and the refining effect of nano CeO2 was better than that of micro CeO2 . The properties of alloys such as Vickers hardness, TRS and fracture toughness increased with the increase of CeO2 additives, and then followed a decrease trend when the content of CeO2 exceeded 0.8%. Furthermore, the content of nano CeO2 greatly affected the cemented carbide and 0.4% of nano CeO2 revealed the strongest improvement on the structure and performances of WC-10Co cemented carbide. Highlights: Micro/nano CeO2 additives are used to mingle WC-10Co cemented carbide. Micro/nano CeO2 content is related to the structure and property of WC-10Co alloy. The strengthening effect of Nano CeO2 is higher than Micro CeO2.